The Effect of Forward Chaining Method towards Self-Help Ability for Wearing Buttoned Clothe for Students with Intellectual Disability in the Grade VII - Arina Rosada Zain; Umi Safiul Ummah; Abdul Huda (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2017)
The purposes of this study were to describe: 1) the ability of self-help in wearing the buttoned shirt before being given the intervention with forward chaining method, 2) the ability of self-help in wearing the buttoned shirt after being given the intervention with forward chaining method, 3) the effect of forward chaining method towards the ability of self-help in wearing the buttoned shirt. The method of this study was an experimental method by using the Single Subject Research (SSR) with A-B-A design. The percentage of overlap between the baseline condition-1 (A1) and the intervention was 0% showing no overlap.Tujuan dari penelitian ini adalah: 1) untuk mendeskripsikan kemampuan peserta didik tunagrahita sedang dalam kemampuan bina diri memakai baju berkancing sebelum diberikan intervensi menggunakan metode forward chaining, 2) untuk mendeskripsikan kemampuan peserta didik tunagrahita sedang dalam kemampuan bina diri memakai baju berkancing setelah diberikan intervensi menggunakan metode forward chaining, 3) pengaruh metode forward chaining terhadap kemampuan bina diri memakai baju berkancing. Metode yang digunakan pada penelitian ini yaitu metode eksperimen dengan menggunakan Single Subject Reseach (SSR) dengan model A-B-A. Presentase overlap antara kondisi baseline-1 (A1) ke intervensi sebesar 0% yang menunjukkan tidak ada tumpang tindih.